Republic of Guinea : Planning, Connecting, Financing in Conakry - World Bank Group (Washington, DC: World Bank, 2019)
This study looks into the challenges and opportunities posed by urbanization in Guinea, reviewing briefly the trends at the national level but focusing on the urban area of Conakry. The main reasons for focusing on the urban area of Conakry are the following. While secondary cities in Guinea are growing economically and in population, Conakry already represents close to 50 percent of the urban population and its demographic growth outpaces that of other urban areas. This creates a sense of urgency to solving the country’s capital problems. Secondly, Conakry remains the country’s main interface for international trade through its port facility. Failure to address Conakry’s issues, including congestion levels, would likely weaken its (and Guinea’s) attractiveness in the long run. Follow-up studies could however look into Guinea’s system of cities, including how they are connected to each other within the country and with their neighbors. The analysis presented in this review shows that urban areas in Guinea, and Conakryin particular are currently not acting as engines of growth and competitiveness and are failing at providing public services and quality living standards for their residents. It argues that the reasons are to be found i) in the business environment which, recent progress aside, stymies private sector job creation and economic diversification, ii) in Conakry’s deficient connectivity system which acts as a bottleneck for residents to have access to economic opportunities, iii) in its obsolete and unenforced planning strategies and its rigid land markets and iv) in the lack of institutional clarity and financial resources which leads to underinvestment in public services.